Property Rights In The Perspective Of The Qur'an (A Comparison Of Ownership In The Capitalist, Socialist And Islamic Economic Systems) - Sudarmi; Abubakar, Achmad; Irham, Muhammad (PT. Maju Malaqbi Makkarana, 2025)
Islamic views on property ownership depart from the notion that individuals have an innate desire to possess property (fithrah), as Islamic societies depend on other people to function. The riches or money that Allah SWT has bestowed upon this universe is a gift to humanity and should be used as efficiently as possible to ensure everyone's financial security. One topic covered in economics classes, including socialism, capitalist, and Islamic economics, is ownership rights. Ownership rights are determined by certain characteristics of each economic system. The number of assets (goods and services) that can be owned is limited under a socialist economy, but the method of acquisition (quality) remains unconstrained. This suggests that you can distribute it in whatever way you want. Meanwhile, the capitalist economic system views property ownership as unlimited, both in terms of quantity and quality; that is, any kind of property ownership is acceptable as long as it does not restrict the freedom of others. Islam acknowledges, but does not fully give, the right of humans to own the materials they use for production and consumption, in contrast to socialism and capitalist economic systems.